2013
DOI: 10.3892/or.2013.2570
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Th17 and Treg cells in gastric cancer patients and its correlation with clinical parameters

Abstract: Th17 cells and CD4+CD25+ regulatory T (Treg) cells have been reported to share reciprocal developmental pathways but exhibit opposite effects, and the balance between them controls inflammation and autoimmune diseases. However, information regarding Th17/Treg cells in cancer-bearing hosts is still limited. In the present study, we investigated the distribution of Th17 cells in relation to Treg cells in gastric cancer patients, and evaluated how the imbalance in Th17/Treg cells in gastric cancer correlates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 35 publications
(43 reference statements)
0
56
0
1
Order By: Relevance
“…28 Even if gastric cancer is frequently associated with Helicobacter pylori-induced gastritis, a high density of Foxp3 C cells is usually associated with a poor prognosis, as found in our present study and predominating the literature. [29][30][31][32] Only Haas et al found a relationship between high levels of Foxp3C cell tumor infiltration and improved prognosis in 52 patients bearing gastric adenocarcinomas of the cardia. 33 In the present work, we did not find a significant correlation between gastric cancer patient survival and the density of CD8 C or IL-17 C tumor-infiltrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…28 Even if gastric cancer is frequently associated with Helicobacter pylori-induced gastritis, a high density of Foxp3 C cells is usually associated with a poor prognosis, as found in our present study and predominating the literature. [29][30][31][32] Only Haas et al found a relationship between high levels of Foxp3C cell tumor infiltration and improved prognosis in 52 patients bearing gastric adenocarcinomas of the cardia. 33 In the present work, we did not find a significant correlation between gastric cancer patient survival and the density of CD8 C or IL-17 C tumor-infiltrating cells.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 and Treg may both exhibit ascending trend with TNM stage, or Treg rather than Th17 increases in advanced gastric cancer (10,31). There are also differences between the distribution of Th17 and Treg in peripheral blood and cancer tissues.…”
Section: Interactions Among the Expression Level Of Il-6 Tgf-β1 Foxmentioning
confidence: 99%
“…The expression of Th17 and Treg in the diseases is related to the factors that influence their differentiation (20,21). Moreover, the function of Th17 and Treg in the diseases depends on the effectors that are synthesized and secreted by them (10,11). The correlation between the factors that induce their differentiation and their effect factors in the disease has not been reported systematically.…”
Section: Interactions Among the Expression Level Of Il-6 Tgf-β1 Foxmentioning
confidence: 99%
See 2 more Smart Citations